Holocene chronology of a continental shelf mudbelt off southwestern Africa - Meadows, M. E.; Rogers, J.; Lee-Throp, J. A.; Bateman, M. D.; Dingle, R. V. (The Holocene, 2002)
The Holocene lithostratigraphy and geochronology of sediments on an inner continental-shelf mudbelt off the west coast of southern Africa is presented. Based on a study of seven large gravity cores, numerous grab samples and two vibracores, two distinctive sections of the mudbelt have been identi” ed. The northern section is associated with the Orange River prodelta, and is dominated by laminated clay-rich sediments, while the southern section off Namaqualand is associated with more homogeneous muds. AMS radiocarbon ages of 31 samples from these cores are problematic due to the absence of expected modern material at the sedimentocean interface and numerous age reversals and inconsistencies in some of the cores. Possible mechanisms to explain the apparently anomalously old surface and near-surface samples are suggested. Most likely expla nations appear to lie in a combination of sediment-retrieval problems, the periodic loss of ” ne particulate organic carbon from within the water column, the sampling of possible relic sediments and, most likely of all, the incorporation into the sediments of 14C-depleted terrigenous organic matter. The age reversals are especially evident in the laminated sediments, and the entrainment of ‘old’ carbon from the terrestrial source of these sediments is offered as the most parsimonious explanation. Stable carbon isotope analyses and a single lumi nescence age support the contention that radiocarbon date inconsistencies are a consequence of terrestrial inputs of carbon which is non-contemporaneous with the actual time of sedimentation. In studies of offshore accumulations of terrigenous material, the marine-derived organic fraction may therefore prove a more reliable measure of radiocarbon chronology.
id: 220